None of the above: lessons to be learnt from the police force structures debate - Godfrey, John (2007)
This article reviews the events of September 2005 to August 2006 through the eyes of a police authority that was involved actively in resisting the former Home Secretary's plan to regionalise police forces. It offers some conclusions on what the experienc;e has to say about the nature of our commitment to the local governance and accountability of the police service, how the position of police authorities within the tripartite structure has been affected by what has happened and how police authorities might be better prepared in future to assert their position on behalf of local communities and to counter continuing centripetal political, managerial and professional pressures for ever larger and ever more remote organisational structures. - Reproduced.
Keywords: Police